Gender Variation of Scapula in a Bangladeshi Population – A Radiological Study - Momena, Zeenatul; Rahman, Md Shamsur; Perveen, Rehana; Shahin, Rebeka; Chowdhury, Mahfuza; Mahmud, Shaila (Community Based Medical Journal, 2023)
The scapula is a complex anatomical unit; it connects the humerus with the clavicle. The scapula presents several variations, based on race, sex and region. Sexual dimorphism plays a key role in forensic anthropology. The scapula is sexually dimorphic and can potentially be used in forensic investigations. A cross-sectional study was conducted under Department of Anatomy, Dhaka Medical College, Dhaka, between July 2017 and June 2018, to observe the morphometric pattern of the left scapula in adult male and female Bangladeshi people for establishment of a baseline anatomical data for future studies. Shoulder radiograph of anterior-posterior view were taken from 100 apparently healthy adult male and female patients aged between 25 and 50 years who were attending the Department of Radiology & Imaging, Dhaka Medical College Hospital, Dhaka. From these images morphological measurements like the length and breadth of left scapula, the lengths of infraspinous line and scapular spine were measured by software named RadiAnt DICOM Viewer. The length and breadth of left scapula, the length of coracoid process, as well as the lengths of infraspinous line and scapular spine were found significantly higher in males. To summarize, a significant difference was observed in morphological measurements of the left scapula between the sexes in Bangladeshi people. CBMJ 2023 January: Vol. 12 No. 01 P: 12-16